Difusi Inovasi Kebijakan PP Tunas: Mengukur Penerimaan dan Adopsi Perlindungan Anak di Ruang Digital - Algooth Putranto; Budi Suswanto; Tri Satria Muhammad; Faruq Umar Haidar; Siti Nuraeni; Fadilah Arya Saputra; Yuniar Yuniar (Asosiasi Dosen Muda Indonesia, 2026)
The escalating access of children to social media has significantly broadened their exposure to cyber risks, a pressing phenomenon to which the government responded by enacting Government Regulation Number 17 of 2025 concerning the Governance of Electronic System Operation for Child Protection (PP TUNAS). This study aims to analyze the innovation diffusion process of the PP TUNAS policy within the broader social system by applying Everett M. Rogers’ theoretical framework. Employing a sequential explanatory mixed-methods design, descriptive quantitative data derived from an EVIDENT Institute survey of 1,050 urban respondents serve as the foundational baseline layer. The robustness of this study relies on a qualitative approach using an interpretive policy discourse analysis grounded in Lasswell’s Communication Model (who, says what, in which channel, to whom, with what effect). This qualitative method critically deconstructs the official regulatory text of PP TUNAS and the respondents' thematic narratives to uncover the root causes of dissonance underlying the statistical figures. The findings indicate that PP TUNAS has successfully progressed through all stages of innovation diffusion. During the knowledge and persuasion phases, the public demonstrated substantial affective support (96.1%), which was followed by autonomous protective measures taken by parents in the implementation stage (91%). Nevertheless, the confirmation stage revealed distinct dissonance regarding the perceived ineffectiveness of digital platforms' age verification systems (59.3%). The qualitative analysis acutely reveals that this dissonance stems from a rupture in the communication chain at the channel level (the platform's technical delivery), even though the policy message (says what) was well-received by the communicants (to whom). The study concludes that the long-term success of PP TUNAS heavily depends on structural rectifications of the platform's technical channels alongside the reinforcement of humanistic family digital literacy programs.